2003
DOI: 10.1086/374843
|View full text |Cite
|
Sign up to set email alerts
|

Inhalational Anthrax Due to Bioterrorism: Would Current Centers for Disease Control and Prevention Guidelines Have Identified the 11 Patients with Inhalational Anthrax from October through November 2001?

Abstract: A panel of 10 physicians used the nominal group technique to assess the ability of the Centers for Disease Control and Prevention (CDC) interim guidelines for clinical evaluation of persons with possible inhalational anthrax (IA) to retrospectively identify the 11 patients with IA seen during the October 2001 bioterrorism outbreak. The guidelines would not have identified 10 of 11 of these patients, primarily because the guidelines were designed to address only those patients with a known history of exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…However, there is typically little evidence of significant bacterial growth within the alveolar space, as is characteristic of classical pneumonia. Today it remains difficult to diagnose inhalational anthrax; many of the 2001 victims of the mailing of anthrax spores in the United States were initially diagnosed with bronchitis or pneumonia (55). Thus, it is not surprising that early research focused on the lungs and trachea.…”
Section: Reforming the Trojan Horse Model In Light Of New Datamentioning
confidence: 99%
“…However, there is typically little evidence of significant bacterial growth within the alveolar space, as is characteristic of classical pneumonia. Today it remains difficult to diagnose inhalational anthrax; many of the 2001 victims of the mailing of anthrax spores in the United States were initially diagnosed with bronchitis or pneumonia (55). Thus, it is not surprising that early research focused on the lungs and trachea.…”
Section: Reforming the Trojan Horse Model In Light Of New Datamentioning
confidence: 99%
“…Other features more common in anthrax were: nausea, vomiting, pallor, cyanosis, diaphoresis, altered level of consciousness, and increased hematocrit level. Two groups 54,55 have developed screening criteria to help diagnose anthrax after a known bioterrorism incident. However, a costeffectiveness analysis showed that although both criteria would have identified cases Christian Abbreviations: CT, computed tomography scan; CXR, chest radiograph; MRI, magnetic resonance imaging.…”
Section: Bacterial Agentsmentioning
confidence: 99%
“…On the other hand, Mayer et al proposed to modify the CDC-issued interim guidelines for clinical evaluation of persons with possible IA (41) on the basis of the epidemiological, clinical, laboratory, and radiologic findings of the 11 patients with bioterrorism-related IA during their first visit to a physician. Whereas the CDC guidelines would not have identified 10/11 of these patients, the proposed extensions of the guidelines retrospectively identified 8/11 of the patients with IA (42). In a recent article, Howell et al compared the two methods proposed to screen for IA, applying them to the emergency department charts of patients who presented with possible signs or symptoms of IA at a hospital.…”
Section: Initial Management Of Hospitalized Casesmentioning
confidence: 99%